Evidence-Based Decision-Making for Intraoral Scanner Selection in Clinical Dental Practice: Development of the EBIOS Pilot Framework - Socratis Thomaidis; Georgios Chrisochoou; Eleni-Ioanna Tzaferi; Aikaterini Petropoulou; Maria Antoniadou (Prosthesis, 2026)
Background/ Objectives: Selecting an intraoral scanner (IOS) has evolved into a complex clinical decision that extends beyond technical performance alone. This study aimed to investigate the clinical, technical, educational, and organizational factors influencing intraoral scanner selection among dentists, evaluate awareness of ISO specifications and evidence-based criteria, and propose a conceptual framework to support evidence-based technology selection. Methods: A cross-sectional questionnaire-based study was conducted among dentists practicing in Greece. A total of 86 questionnaires were returned from 271 invited participants (response rate: 31.73%). Valid sample sizes varied across analyses according to item applicability and analyzable responses. The questionnaire assessed demographic and professional characteristics, intraoral scanner use, selection criteria, awareness of ISO specifications, educational background, and evidence-related factors. Composite indices were developed to evaluate the principal decision-making dimensions. Results: Technical and clinical performance-related criteria received the highest importance ratings in intraoral scanner selection. Although participants generally reported good perceived knowledge of intraoral scanners, only 35.7% reported awareness of ISO specifications. Dentists familiar with ISO standards assigned significantly greater importance to specification-related and safety-related criteria, suggesting an association between reported ISO awareness and greater emphasis on specification- and safety-related selection criteria. Continuing professional education represented the predominant source of knowledge acquisition. Based on the integration of these findings, the EBIOS Pilot Framework (Evidence-Based Intraoral Scanner Selection Framework) is proposed as a preliminary conceptual synthesis of factors potentially relevant to evidence-informed intraoral scanner selection. Conclusions: The findings suggest that intraoral scanner selection may be understood as a multidimensional decision-making process involving technical performance, scientific evidence, professional education, and standardized quality criteria. The proposed EBIOS Pilot Framework provides a preliminary conceptual basis for future validation and refinement in larger, independent populations.